DIGITALISASI UMKM : STRATEGI PENDAFTARAN LOKASI BISNIS DI GOOGLE MAPS UNTUK MENINGKATKAN DAYA SAING LOKAL - Setyawati, Mely; Elisa, Kustina; Farit Ghozali, Ahmat; Rahmawati, Zuli Dwi; Junaidi, Mahbub (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The Community Service Program (KKN) in Dibee Village, Lamongan, was implemented to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) by registering business locations on Google Maps. The activities included seminars, field surveys, and assistance in creating Google Business profiles containing business information, operating hours, and product photos. This initiative was designed to expand online visibility, making it easier for consumers, particularly those from outside the village, to access local products. A participatory approach was applied to encourage MSME actors to actively manage their digital profiles. Consequently, the program not only provided short-term benefits in terms of online promotion but also strengthened the capacity of MSME actors to independently sustain their digital business presence. The outcomes of this program support Dibee Village’s transition toward a more adaptive, competitive, and sustainable digital economy ecosystem.